Ethical values for digital-age learners - Mehedi Shahnewaz Jalil, Suriana, Desi Purnama Sari, Cut Intan Salasiah, Ranti Maulya , Suriana (JKA, 2024)
It is vital for students to study digital ethics material in today's technological age. They need to understand how digital ethics are important to maintaining the security and privacy of personal data, building a good digital culture, and enhancing their digital literacy skills. The head of school can also play an important role in supporting teachers and students in applying digital ethics. The head of school should provide digital ethics education to teachers and students to ensure they understand how to guide students in using digital media and instill ethics in them. Teachers can teach digital ethics materials by integrating digital literacy into the curriculum, utilizing digital resources, providing hands-on teaching, and facilitating discussions. In order to be able to adapt to the changes taking place in the digital age, students must understand digital ethics.